Enhancing stability of animal production systems - Fitzhugh, H.A. (Society for the Advancement of Breeding Researches in Asia and Oceania, 2001)
Demand for meat and milk will more than double in Asia by 2010, as will the consumption of feed grain by livestock. This is the Livestock Revolution. Because most of the meat, milk and feed to supply this demand will be produced by Asian farmers, the Livestock Revolution can enable smallholders-livestock and grain-producers to generate income and build assets. Moreover, their livestock may provide draft power and contribute to nutrient cycling to build soil fertility at farm level. On the negative side, the Livestock Revolution is causing environmental problems through loss of biodiversity, degradation of soil and water and production of greenhouse gases. The future stability-economic and environmental- of livestock production systems in Asia is inextricably linked to the stability of crop production and markets in the region. Research to ensure sustainable livestock Development must follow an interdisciplinary systems approach incorporating the best science from socioeconomic, ecological, crop, agronomic and livestock scientists from national and international R & D [research and Development] organization from both public and private sectors ILRI [International Livestock Research Inst.] is working with partners to provide research-based interventions to enhance the stability of livestock production systems in Asia.